2022
DOI: 10.5455/njcm.20201213064554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Covid-19 Pandemic on the Mental Health and Lifestyle of Health Care Workers in Southern India

Abstract: Introduction: The Covid-19, just like any other Pandemic has been an extremely difficult time for people all over the world; however it has been the most challenging time for the frontline staff such as health care workers. It has not just led to changes in their work environment, but has also affected their lifestyle and mental health. Objective: We conducted this survey to analyse the impact of the covid-19 pandemic on the lifestyle and mental health of health care workers. Methodology: A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…[ 4 - 26 ] The number of articles included in the pooled analysis of insomnia was 16. [ 7 , 13 , 14 , 20 , 22 , 26 - 36 ] The total sample size for the meta-analysis of stress and insomnia is 8125 and 4974, respectively. Some studies were conducted at pan-India levels, and some were in specific states.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 - 26 ] The number of articles included in the pooled analysis of insomnia was 16. [ 7 , 13 , 14 , 20 , 22 , 26 - 36 ] The total sample size for the meta-analysis of stress and insomnia is 8125 and 4974, respectively. Some studies were conducted at pan-India levels, and some were in specific states.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 - 49 ] Out of the thirty-five studies, five studies did not specifically mention the prevalence of any of the outcome measures such as depression, anxiety, stress, and insomnia therefore not included in the meta-analysis. [ 32 , 39 , 43 , 44 , 49 ] The prevalence rate of anxiety is reported in twenty studies[ 15 - 17 , 19 , 20 , 23 , 27 , 29 , 31 , 33 - 36 , 40 - 42 , 45 - 48 ] whereas twenty-one and twenty-two studies reported the prevalence rate of depression[ 15 - 17 , 19 , 20 , 23 , 25 , 27 , 29 , 31 , 33 , 35 , 37 , 38 , 40 - 42 , 45 - 48 ] and stress[ 15 , 16 , 18 , 19 , 21 - 24 , 26 , 28 - 31 , 33 , 37 , 38 , 40 , 41 , 45 - 48 ] respectively. There are six studies available with accurate data on the prevalence of insomnia.…”
Section: R Esultsmentioning
confidence: 99%